THE IDEOGRAPHIC FIELD OF ENGLISH AND KARAKALPAK COMPARISONS DESCRIBING A PERSON - Usenova, G.A. (SCIENCE and SOCIETY, 2026)
Comparisons are a powerful linguistic tool that not only convey information but also create a vivid, memorable image. In the English and Karakalpak languages, there is a rich arsenal of comparisons used to describe various aspects of a person’s personality: appearance, character, behavior, intelligence, etc. This article is devoted to the study of the ideographic field of English and Karakalpak comparisons describing a person, with an emphasis on imagery, cultural connotations, and the evolution of these expressions. We will analyze a wide range of examples, classifying them into thematic groups and identifying the dominant metaphors underlying these comparisons.
Keywords: comparisons describing a person; ideographic field; the English and Karakalpak languages